Classical Heritage and European Identities The Imagined Geographies of Danish Classicism - Andersen Funder, Lærke Maria (Taylor & Francis, 2019)
This book examines how different agents and institutions within the Danish nation state have situated themselves within this complex landscape of competing appropriations of classical antiquity from the eighteenth century to the present day. In particular, it focuses on the use of classical heritages to construct both European and national identities (in the plural) and especially on how Danes in this period have engaged with a sense of European commonality through their engagements with the classical past